No end of history : a Chinese alternative concept of international order? - Godehardt, Nadine (2016)
Zusammenfassung: There is no end of history. Francis Fukuyama's famous claim has turned into quite the opposite. Today, liberal democracies and the Western concept of international order are being permanently challenged by an increase in political and economic crises, global and local dissent with established mechanisms of international affairs, and other political ideologies. These challenges increase the leverage of newly emerging actors such as China to push forward alternative ideas of international order. Among all the different Chinese foreign policy initiatives announced by President Xi Jinping, China's “One Belt, One Road” initiative clearly stands out. It is by far the most comprehensive and visible Chinese initiative of the last three years. China's OBOR initiative is regarded as a vision for building up a comprehensive cultural, economic, and political network that promotes connectivity and cooperation between countries, regions, and cities along the Silk Road. Furthermore, the OBOR initiative is flexible, inclusive, and open. OBOR has the potential to grow into an alternative idea showing how the common space of international politics could be organized in the future. Consequently, OBOR challenges the still dominating Western vision of the international system and could effectively transform the existing structure of the current international order. For this reason, this study aims to conceptualize China's OBOR initiative in a broader context. Instead of only focusing on specific mechanisms linked to OBOR, such as, for example, the Asia Infrastructure Investment Bank, it develops an analytical approach that also highlights the various dimensions of China's OBOR initiative. (SWP Research Paper)